Penerapan Digital Marketing Sebagai Strategi Peningkatan Penjualan Skincare Herbal SR12 - Fivtinima Wya Muflikhata; Wirawan Fadly (Journal of Economics, Law, and Humanities, 2023)
This research is motivated by the significant turnover obtained from the leading distributors and agents through digital marketing strategies. SR12 (Skin Relieve 12) Herbal Skincare only in Ponorogo. This study uses field research using a qualitative approach, with data collection techniques through observation and interviews. This writing aims to find out how to apply Islamic digital marketing strategies in increasing sales of SR12 Herbal Skincare products, how the results of implementing Islamic SR12 Herbal Skincare Islamic digital marketing strategies, and analysis of inhibiting and supporting factors of SR12 Herbal Skincare Islamic digital marketing strategies. The results showed the application of the Islamic digital marketing strategy SR12 Herbal Skincare in increasing their sales using digital social. While the development of implementing this Islamic digital marketing strategy is that SR12 Herbal Skincare is carried out with a design that includes segmenting, targeting, and positioning (STP). In carrying out the process, the company covers a wide range, while the inhibiting factors include using digital social media, each of which has obstacles.